Keputusan Investasi, Keputusan Pendanaan, Kebijakan Deviden, Profitabilitas, Firm Size, dan Nilai Perusahaan pada Sektor Aneka Industri di Bursa Efek Indonesia - Baskoro Langgeng Pamuji; Ulil Hartono (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
This study aims to examine the effect of investment decisions, funding decisions, dividend policy, profitability and company size on firm value. In this study, company value is measured by Price to Book Value (PBV), Price Earning Ratio (PER) is used as a proxy for investment decisions, Debt to Equity Ratio (DER) is used as a proxy for funding decisions, Devided Payout Ratio (DPR) is used as a proxy dividend policy, Return On Equity (ROE) is used as a proxy for profitability and natural logarithm (ln) is used as a proxy for measure of firm value. This study uses a purposive sampling method to determine the number of samples. The sample used in this study were 10 manufacturing companies listed on the Indonesia Stock Exchange which published financial statements for the 2013-2017. The data analysis method uses multiple regression. The results showed that investment decisions had a positive effect on firm value. However, funding decisions had no effct on firm value, dividend policy had a negatif effect on firm value, profit had a positive effect on firm value and company size had a negatif affect the firm's value.